The Most Optimal Transportation Policy to Address Carbon Emissions: A Bibliometric Analysis, Benchmarking, and Future Research Plan - Tiara Nugrahayani; Rifqi Raza Bunahri; Musri Kona; Dhian Supardam; Hadi Prayitno (Dinasti International Journal of Management Science, 2023)
This research article examines the role of transportation policies in reducing carbon emissions, focusing on various cities in Indonesia. The study aims to identify the most optimal transportation policies to address carbon emissions and promote environmentally friendly urban development. Bibliometric methods quantitatively analyzed scholarly literature on transportation policies and carbon emissions, while benchmarking methods compared transportation policies worldwide based on carbon emission data and air quality. A total of 100 articles were found in the Scopus database using the keywords 'transportation policy city carbon emission' from 2018 to 2023. The selection was refined to 50 articles with the highest citations and further narrowed down to 31 articles, then to 10 articles focusing on specific city research, and finally to the top 5 articles in Scopus Q1 journals (journals with the highest academic quality and impact) based on benchmarking results as the basis for policymaking. The research results indicate four optimal transportation policy recommendations to address carbon emissions: urban-scale fossil fuel consumption calculations, spatial planning prioritizing sustainable transportation, the use of micro-electric vehicles (micromobility), and increased energy efficiency in transportation. The study also identified under-researched variables related to carbon emission reduction efforts, such as urban airports, climate change mitigation, low-carbon mobility transition, and other future research formulation plans that can be further investigated. This research underscores the urgency of prioritizing the development of sustainable transportation policies to reduce carbon emissions and improve air quality in Indonesian cities.